ANALISIS TOKOH FADILLAH SECARA ANALITIS DAN DRAMATIK DALAM NOVEL BERJUDUL “IMIPRAMINE“ KARYA NOVA RIYANTI YUSUF - Nita Fauziah; Aditya Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study aims to (1) discuss the results of characterization analysis in Fadillah figures in an analytical novel titled “Impramine”, and (2) describe the characterization of Fadillah dramatically. Nova Riyanti Yusuf’s work novels will be analyzed qualitatively. As for the research steps include: (1) reading the novel “Impramine”, (2) analyzing the characterization of the Fadillah figures in the novel, (3) describing the characterization of the character analytically and dramatically. Based on the results of the analysis, it can be seen that Nova Riyanti Yusuf created the characterization of Fadillah with analytical and dramatic figures depicting techniques.